Monolayer Field‐Effect Transistors of Nonplanar Organic Semiconductors with Brickwork Arrangement. (27th April 2015) - Shan, Liang; Liu, Danqing; Li, Hao; Xu, Xiaomin; Shan, Bowen; Xu, Jian‐Bin; Miao, Qian
<x xml:space="preserve">Abstract</x> Twisted hexabenzoperylenes (HBPs) that are equipped with four methoxyl groups and two alkyl chains self‐assemble into lamellar semiconductors with an unusual brickwork arrangement of twisted π‐faces. As a result of this brickwork arrangement, through a dip‐coating process, these HBPs easily form one‐molecule‐thick nanosheets that behave as p‐type organic semiconductors in monolayer transistors with field‐effect mobility of up to 0.076 cm2 V−1 s−1.